2006
DOI: 10.28945/2952
|View full text |Cite
|
Sign up to set email alerts
|

Would Regulation of Web Site Privacy Policy Statements Increase Consumer Trust?

Abstract: Proponents of e-commerce have known for some time that limited participation by consumers partially reflects their concern over the privacy of personal information. To address consumer concerns, web site operators have employed security mechanisms, including privacy policy statements to increase their perceived trustworthiness. While empirical evidence is limited, there is some question regarding the ability of privacy policy statements to engender significantly greater levels of trust. The limited effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Although this survey reveals that not all respondents read online privacy statements, confirming results of previous studies (Arcand et al, 2007;Jensen et al, 2005;Meinert et al, 2004), it is worth noting that respondents consider the availability and the accessibility or findability of a privacy statement as indicators of a municipality's trustworthiness in terms of how it uses and processes users' personal data. The presence and the ease of finding an online privacy statement are sufficient to prompt most respondents to disclose requested personal data.…”
Section: Discussion and Research Implicationssupporting
confidence: 84%
See 3 more Smart Citations
“…Although this survey reveals that not all respondents read online privacy statements, confirming results of previous studies (Arcand et al, 2007;Jensen et al, 2005;Meinert et al, 2004), it is worth noting that respondents consider the availability and the accessibility or findability of a privacy statement as indicators of a municipality's trustworthiness in terms of how it uses and processes users' personal data. The presence and the ease of finding an online privacy statement are sufficient to prompt most respondents to disclose requested personal data.…”
Section: Discussion and Research Implicationssupporting
confidence: 84%
“…Although it is also known that most Internet users do not bother to read privacy statements (Arcand et al, 2007;Jensen, Potts, & Jensen, 2005;Meinert, et al, 2004;, they are most likely to trust organizations that post privacy statements on their websites (Pan & Zinkhan, 2006) and would feel greater control over their personal data when shared to organizations with websites that post privacy statements (Arcand et la., 2007). Aside from online privacy statements, Internet seals of approval from third-party certifying organizations, which help in endorsing organizational policies on privacy and security, have also been found to improve users' positive evaluation of the privacy practices of online organizations behind websites with those seals (Miyazaki & Krishnamurthy, 2002) and to encourage online information disclosure (LaRose & Rifon, 2007).…”
Section: Trust and The Lack Thereof: Their Impact On Information Withmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that studies have shown that users fail to read sites' privacy policies [22,27], the kinds of minimum protections these laws put in place are particularly important. Previous research has shown that legislation can have mixed effects on policies, especially their readability and usability [3,22].…”
Section: Related Workmentioning
confidence: 99%